UMP, AspenTech develop Academia-Industry Competency Programme - Siti Nur Azwin, Zulkapri (2022)
KUANTAN, 25 July 2022 - Universiti Malaysia Pahang (UMP) and Aspen Technology (AspenTech) are expanding university and industry collaboration in the field of academia, research, industry networks and communities with the signing of a memorandum of agreement (MoA) on 1 November 2021.